A comparative analysis of some Albayukinmetekih variables and efficiency ratio between certain types of skill transmission game of volleyball - Mohsen , Alaa (Journal of Physical Education, 2011)
The main aims of the research are: Knowing the differences in Some biomechanical variables between the standing float serving in the volleyball game , knowing the differences in the percentage of effectiveness between the skill of standing float serving and the jump float serving in the volleyball game . The importance and need for the research arises in giving the specific information about the percentage of effectiveness of some types of the serving skill during performance and comparing it with some biomechanical variables of these types, so that knowing whether the existence or not of the differences in these variables with the percentage of effectiveness of serving skill . The researcher has chosen the subjects on purpose of (14) fourteen players representing in advance players of industry team club and police team club that participate in the elite volleyball league for the sport reason2009-2010, the main test has done on 25/7/2010. The researcher has used a video camera of 25photsec. These results have been analyzed and got the biomechanical variables by Dartfish program,the researcher has got many results. The most important result is showing the immaterial differences for the jump float serving in the variables of (the ball launching speed, the shoulder joint angle speed, the ball launching distance and the highest point of ball hitting moment and the percentage of effectiveness).In addition ,immaterial differences are shown in the standing float serving in the variables of (the hip angle in the moment of ball hitting and the ball launching angle). The researcher has many recommendations. The most important are: the necessity of coaches and players caring of using jump float serving skill to achieve the highest percentage of effectiveness of stand float serving success in the ball strength and speed in stand float serving, although the simplicity of performing it in comparison with the spiking serving.